Can Lactobacillus fermentum LF10 and Lactobacillus acidophilus LA02 in a slow-release vaginal product be useful for prevention of recurrent vulvovaginal candidiasis?: A clinical study. - Murina, Filippo; Graziottin, Alessandra; Vicariotto, Franco; De Seta, Francesco (J Clin Gastroenterol, 2014)
OBJECTIVE: To assess the effectiveness of the association of 2 specific strains, Lactobacillus fermentum LF10 (DSM 19187) and Lactobacillus acidophilus LA02 (DSM 21717), specifically formulated in slow-release effervescent tablets, in patients with recurrent vulvovaginal candidiasis. STUDY DESIGN: The study was a clinical trial of 58 women diagnosed with recurrent VVC (≥4 culture-confirmed episodes in a 12-mo period). All patients were given 200 mg of fluconazole orally as an induction dose for 3 alternate days during the first treatment week. Afterward, the patients were given a new product formulated in slow-release vaginal tablets containing at least 0.4 billion live cells of each of lactobacillus L. fermentum LF10 and L. acidophilus LA02 (first phase of the prophylactic period), on alternate days for 10 consecutive nights. Patients who were still free of symptoms were given 1 vaginal tablet every week for the next 10 weeks (second phase of the prophylactic period). Patients asymptomatic after the total duration of the observation phase (7 mo) were considered as responders. RESULTS: During the second 10-week prophylactic phase, 49 of 57 (86.0%) patients remained free of clinical recurrence, whereas symptomatic VVC occurred in 8 patients (14.0%). During the 7-month follow-up, 42 patients of 49 (85.7%) were symptom free at the end of the protocol, whereas clinical recurrences occurred in 7 women (14.3%). Overall, 42 of 58 women enrolled in the study (72.4%) experienced no clinical recurrence throughout the 7-month observation phase (responders). CONCLUSIONS: This study strengthens the evidence supporting the use of specific lactobacilli with well-demonstrated activities associated with the creation and maintenance of a vaginal biofilm that hinders the persistence of an infection caused by Candida.
Keywords: Administration, Intravaginal; Adult; Biofilms; Candidiasis, Vulvovaginal; Delayed-Action Preparations; Female; Humans; Italy; Lactobacillus acidophilus; Lactobacillus fermentum; Middle Aged; Probiotics; Recurrence; Tablets; Time Factors; Treatment Outcome; Vagina; Vulva; Young Adult